2013
DOI: 10.1517/14728222.2013.778829
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis reveals functional pathways of glatiramer acetate activation

Abstract: GA-induced functional pathways coincide with known mechanisms of GA activity in MS patients and further support the unique therapeutic effect of this drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 37 publications
5
45
1
4
Order By: Relevance
“…It is important to note that GA also bound to a small percentage of monocytes (5-15%) and CD4 + T cells (3-10%) but very few, if any, CD8 + T cells or natural killer cells (data not shown). This binding data supports others work showing effects of GA on various immune cell populations [25,27,28,31,36,37,39]. An interesting finding is that a shift in the negative population not observed with the fluorochrome alone, termed GA lo , was observed when B lymphocytes were incubated with GA ( Figures 1A and 1C).…”
Section: Ga Binds To the B Cell Receptor And In Vivo Administration supporting
confidence: 91%
“…It is important to note that GA also bound to a small percentage of monocytes (5-15%) and CD4 + T cells (3-10%) but very few, if any, CD8 + T cells or natural killer cells (data not shown). This binding data supports others work showing effects of GA on various immune cell populations [25,27,28,31,36,37,39]. An interesting finding is that a shift in the negative population not observed with the fluorochrome alone, termed GA lo , was observed when B lymphocytes were incubated with GA ( Figures 1A and 1C).…”
Section: Ga Binds To the B Cell Receptor And In Vivo Administration supporting
confidence: 91%
“…Although common nonspecific analytical methods can indicate similarities between Copaxone ® and purported generic GA products, they also identify important differences in physicochemical properties, including mixture composition, polypeptide sizes, and charge distribution. Similarly, gene expression studies show profoundly different gene transcription profiles from GA-activated mouse splenocytes when re-activated ex vivo with GA, from transcription profiles when splenocytes are re-activated with purported generic GA product (Bakshi et al 2013;Towfic et al 2014;Citizens petition 2013Citizens petition , 2014. Moreover, gene expression analysis has shown that at least one purported generic GA product (Glatimer ® ) with multiple different marketed batches ( N > 10) demonstrates very poor batch-to-batch consistency of biological effects (Bakshi et al 2013;Nicholas 2012;Towfic et al 2014;Citizen Petition 2009).…”
Section: Glatiramer Acetatementioning
confidence: 99%
“…However, important differences from Copaxone ® have been detected using sophisticated state-of-the-art technologies (Bakshi et al 2013;Towfic et al 2014). As described here, information gleaned by comparing Copaxone ® with some of the purported generic GA products is contributing to a better understanding of the complexity of glatiramoids, and of the crucial relationship between drug manufacture and drug identity and quality for members of the glatiramoid class furthermore, the biological and clinical implications of lack of sameness have been examplified in Teva's multiple publications and citizen petitions.…”
Section: Introductionmentioning
confidence: 99%
“…Соот-ветственно, проведение фармакокинетических исследо-ваний для установления биоэквивалентности ГА-подоб-ных препаратов с оригинальным препаратом (Копак-сон ® -Тева) не представляется возможным. До настояще-го времени не выявлены валидированные биомаркеры для оценки эффективности препарата [15]. Копаксон ® -Тева был создан в ходе экспериментов, в которых изучали действие различных антигенов, применяе-мых для воспроизводства экспериментального аутоиммун-ного энцефалита (ЭАЭ) у мышей в Институте имени Вейц-мана (Реховот, Израиль).…”
unclassified
“…Поскольку биомаркеры ответа и маркеры фармакоди-намики ГА до сих пор не разработаны [15], трудно провести его сравнение с другими глатирамоидами. Ряд авторов раз-работали инновационные расчетные методы, которые могут надежно охарактеризовать различия иммунологического воздействия ГА и ГА-подобных препаратов.…”
unclassified